1990
DOI: 10.1002/art.1780331208
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the effects of interleukin‐1 on glycosaminoglycan synthesis by the urine‐derived interleukin‐1 inhibitor, but not by interleukin‐6

Abstract: Interleukin-1 (IL-1) has been shown to regulate glycosaminoglycan (GAG) synthesis. We therefore investigated whether an IL-1 inhibitor or IL-6 modulates IL-1 biologic activities in human synovial cells and cultured articular cartilage. We found that in the presence of a constant amount of IL-lP, stimulation of hyaluronic acid (HA) synthesis by the IL-1 inhibitor was inhibited in a dose-dependent manner. Similarly, the decrease in sulfated GAG synthesis induced by IL-1 was reversed by the addition of the IL-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Synoviocytes are exquisitely sensitive to mediators of inflammation, such as TNF and IL-1β, and react strongly to direct contact with inflammatory T cells [1,2,3,4,5,6,35]. They are able to secrete numerous proinflammatory molecules, such as PGE 2 , chemokines (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Synoviocytes are exquisitely sensitive to mediators of inflammation, such as TNF and IL-1β, and react strongly to direct contact with inflammatory T cells [1,2,3,4,5,6,35]. They are able to secrete numerous proinflammatory molecules, such as PGE 2 , chemokines (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…CNTFRa has a limited tissue distribution and has been found only in neural, muscular, and hepatic tissues (35,36). reported that IL-6 does not induce PGE2 in peripheral tissues (37)(38)(39). Nevertheless, the pyrogenicity of CNTF was blocked by indomethacin, suggesting that CNTF-like IL-1, TNF, IFN, and IL-6-causes fever by inducing the synthesis of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…When compared on a molar basis in this system, the inhibition by IL-1 was much stronger than that afforded by TNFα (which had a very small effect) and interferon-γ (which had no effect at all). Of importance, the inhibitory effect of IL-1 on this repair process was restored when IL-1Ra was added at adequate concentrations [29].…”
Section: Relative Roles Of Il-1 and Tnfα In Inflammation And Destructionmentioning
confidence: 99%